Concepções e práticas de avaliação do ensino-aprendizagem: foco no PROEJA. - Leal, Maria Lindalva Gomes (2014)
This study had as its focus of investigation the high school integrated with technical vocational Educational program for young and adults (Proeja), which aims at offering professional training integrated with high school education for those who have just finished elementary school and for those who have not graduated from high school yet. The object of this study was the learning assessment concepts and practices developed by the Proeja Refrigeration Course faculty at the Federal Institute of Education, Science and Technology of Ceara (IFCE). For the theoretical background, many theorists of the fields of interest have been referred, such as Silva (2002), Apple (2006) Moreira (2011), Mendez, (2002), Santomé (1995), Gadotti (2008), Freire (2011), Adorno, (2010) Lima (2008), Vianna (2007), Firme (1994), Luckesi (2011), Fernandes (2008), Gatti (2003), Hadji (2001), e Perrenoud (1999), among others. We have opted for the critical interpretive approach which opposes itself to dogmatism, reductionism and is always open and unfinished. In order to analyze the assessment practice, we have used the qualitative methodology to understand the phenomenon under investigation. The Critical Theory that guided this study was used as support of development, signaling what is indispensable to be known, the context in which knowledge is generated, and the defined intentions. The research was developed by using the following procedures: semi-structured interviews, documental analyses, direct observation and a structured survey. The technique used for interpreting the data collected was the analysis of content which enabled the definition of categories through the examination of the answers given by the subjects surveyed. The results analyzed from the categories that arose from the subjects’ answers elucidated the existing contradictions between what is prescribed in the Proeja Basic Document (2007) and the Curricular Design of the Refrigeration and Acclimatization Proeja Course at the IFCE concerning the Learning Assessment concepts and its faculty’s assessment practice effectiveness. Moreover, they have indicated the confirmation of the announced thesis: “that in the Proeja faculty’s assessment practices at the IFCE Fortaleza campus, there is a predominance of the learning verification perspective instead of formative evaluation”. With the result of this research, we have intended to contribute pointing out possible ways for the development of the Proeja assessment practices by starting a discussion process that aimed the enlargement of assessment concepts towards a dialogical and formative evaluation which highlights the assessment knowledge permanent reconstruction.